Archive of tongues : an intimate history of brownness - Charania, Moon, 1976- (Duke University Press, 2023)
"In this deeply intimate book, Moon Charania brings us into an archive of a brown femininized maternal world. Focusing on her mother, a Pakistani woman in diaspora, Charania offers alternative ways of seeing and hearing a migrant woman of color that is not in the service of empire, white hegemony, and neoliberal narrative capital. Her mother's memories, feelings, and stories of abjection, sexuality, connection, and debility reveal ways in which brown women develop survival mechanisms and strategies that are often lived out invisibly, in intimate spaces. Moving through intimate geographies of India, Pakistan, Bangladesh, England, and the United States, Archive of Tongues reveals the everyday fraught terrain of feminine dispossession and the diasporic condition. Opening with a childhood story about tongues, Charania conceptualizes the tongue as an object of theory, a formative project of knowledge, and as an analytic to better inquire into brownness. Charania offers her mother's tongue and her mother's life to recover otherwise silenced stories of sexuality, violence, domesticity, anti-brownness, and anti-blackness"--